Case Report: Application of the LVIS stent as a bridging device for salvage treatment of malapposed lattice flow diverter in a giant posterior circulation aneurysm: technical note and clinical efficacy - Rao, Musheng; Lin, Guan; Cai, Shuzhou (Frontiers in Surgery, 2026)
ObjectiveTo evaluate the feasibility, technical nuances, and clinical outcomes of using the LVIS stent as a bridging device for the salvage treatment of a malapposed Lattice flow diverter (FD) in a giant posterior circulation aneurysm.MethodsWe present a detailed case report of a patient with a giant aneurysm in the V4 segment of the vertebral artery. Following implantation of a Lattice blood flow diverter and coils, immediate post-procedural angiography revealed incomplete opening and malapposition at the proximal segment of the stent, accompanied by delayed distal flow. After unsuccessful attempts to improve wall apposition via microcatheter massage, a salvage strategy was employed by deploying an LVIS stent within the malapposed FD segment. This approach aimed to enhance overall wall apposition and metal coverage to achieve ultimate aneurysm occlusion.ResultsThe salvage procedure was performed successfully. The LVIS stent was accurately deployed within the malapposed segment of the FD. Angiographic assessment after the procedure demonstrated complete wall apposition of the composite stent construct and total occlusion of the aneurysm sac. The patient experienced no new neurological deficits during the perioperative period. Short-term follow-up indicated an excellent clinical outcome, with a modified Rankin Scale score of 0.ConclusionUtilizing the LVIS stent as a bridging salvage strategy is a safe and effective technical option for managing malapposed FDs in complex giant posterior circulation aneurysms. This technique effectively enhances stent wall apposition and structural integrity, potentially promoting intra-aneurysmal thrombosis and eventual occlusion. It provides a valuable clinical approach for managing this challenging complication.